'Diaspora noire': De l'état des lieux à une approche comparatiste dans les littératures africaine francophone et afro-américaine. (1st September 2018) - Adjoumani, A. Mia Élise
This article is a contribution to the debate on the relevance and actuality of the use of the term 'black diaspora' to refer to black populations scattered throughout the world. Limited to the African American population and that of the African diaspora in Europe, the analysis aims to examine the concept of 'black diaspora' through a comparative reading of African and African American fictional texts. The fundamental question is whether the term diaspora, supposing 'the maintenance of a community consciousness beyond dispersal', can gather Africans and African Americans, knowing that the link of these one with Africa goes back several centuries. The hypothesis developed in this reflection is that this filiation, rather than being analysed with regard to the upholding and maintenance of african origins, could be sought in the current living conditions of these two populations.